Pengaruh Charismatic Leadership, Communication Organization, dan Work-Life Balance terhadap kinerja karyawan pada Perusahaan Lembaga Manajemen Infaq (LMI) di Indonesia - ramli, Divo Affan Syahputra; Tri Andjarwati (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study aims to test and analyze the Influence of Charismatic Leadership, Communication Organization, and Work Life Balance on Employee Performance at the Infaq Management Institution Company. With a sample of 86 respondents collected using a questionnaire and the data analysis techniques used were Descriptive Test, Instrument Test, Classical Assumption Test, and Hypothesis Test with SPSS 26. This study was conducted from October - November 2024.The results of this study are that Charismatic Leadership partially has no significant effect on Employee Performance, Communication Organization partially has a positive and significant effect on Employee Performance, and Work-Life Balance partially has a positive and significant effect on Employee Performance at the Infaq Management Institute.Keyword : Charismatic Leadership Communication Organization, Work-Life Balance, Employee Performance